Creating an operational framework for digital multi-disciplinary oral health promotion in children - the ODA pilot in Kuopio public oral health care - Palander, Anni; Liukkonen, Heidi; Miettinen, Tuula; Rajamaa, Maija; Savolainen, Katariina (Finnish Journal of eHealth and eWelfare, 2018)
Health care professionals are in the front line to identify signals of life issues. In Finnish school healthcare 25% of the children are raising concern from the professional’s perspective. In oral health care, ill oral health may be an indicator of issues and vice versa. However, the early inter-professional cross-talk is minimal. The aim of this project was to recognize the patients that would raise concern among oral health care professionals. Holistic interventions of these patients would secondarily improve oral health. Targeting the group with heaviest disease and social burden, the morbidity would cease in the total population. The staff of Kuopio public oral health care was trained for early patient recognition and referral to an oral health intervention clinic. The clinic focused on speaking out the patient’s life situation and individual oral health education. If needed, a multi-professional primary healthcare support team was gathered. With the most complex problems, the family services and child protection services were consulted. In 2017 and 2018 there were 264 and 344 recognized concerning individuals. Through tailored intervention strategies, the target group was able to increase brushing, lower the plague index and improve self-reported oral health (SOH). Total population indicators (decayed-missing-filled index, DMFT and invasive treatment) showed decreasing trends but have too many background variables for reliable effect assessment. Oral health can play an integral role in recognizing compromised individuals. The operational changes created during the project will act as platform for future digital tools.